An incidental finding of unroofed coronary sinus during angiography confirmed by 3D echocardiography; A case report. Issue 8 (3rd August 2022) - Fazlinezhad, Afsoon; Keihanian, Faeze; Ahmadi, Mostafa; Tayyebi, Mohammad
Abstract: Unroofed coronary sinus (UCS) is an uncommon congenital heart anomaly and the most unusual type of atrial septal defect. This report presents a 71‐year‐old female with palpitation and dyspnea following an emotional stress, who was referred for ablation of typical atrial flutter. Finally diagnosed with a partially unroofed CS causing a bidirectional shunt.